(untitled) (Quinto Sol, 2013)
This paper aims to present the need to introduce recent History in the secondary school curriculum, discuss the difficulties implied in such decision, challenge the objections raised by the “Historical Corporation” and advocate for its importance in the development of individuals as citizens.